Gd-AAZTA-MADEC, an improved blood pool agent for DCE-MRI studies on mice on 1 T scanners. (January 2016) - Longo, Dario Livio; Arena, Francesca; Consolino, Lorena; Minazzi, Paolo; Geninatti-Crich, Simonetta; Giovenzana, Giovanni Battista; Aime, Silvio
Abstract: A novel MRI blood-pool contrast agent (Gd-AAZTA-MADEC) has been compared with established blood pool agents for tumor contrast enhanced images and angiography. Synthesis, relaxometric properties, albumin binding affinity and pharmacokinetic profiles are reported. For in vivo studies, angiographic images and tumor contrast enhanced images were acquired on mice with benchtop 1T-MRI scanners and compared with MS-325, B22956/1 and B25716/1. The design of this contrast agent involved the elongation of the spacer between the targeting deoxycholic acid moiety and the Gd-AAZTA imaging reporting unit that drastically changed either the binding affinity to albumin (KA (HSA) = 8.3 × 10 5 M −1 ) and the hydration state of the Gd ion (q = 2) in comparison to the recently reported B25716/1. The very markedly high binding affinity towards mouse and human serum albumins resulted in peculiar pharmacokinetics and relaxometric properties. The NMRD profiles clearly indicated that maximum efficiency is attainable at magnetic field strength of 1 T. In vivo studies showed high enhancement of the vasculature and a prolonged accumulation inside tumor. The herein reported pre-clinical imaging studies show that a great benefit arises from the combination of a benchtop MRI scanner operating at 1 T and the albumin-binding Gd-AAZTA-MADEC complex, for pursuing enhanced angiography and improved characterization of tumor vascular microenvironment.